1976
DOI: 10.1093/infdis/135.supplement_2.s316
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Clinical Studies with Amikacin, a New Aminoglycoside Antibiotic

Abstract: Pharmacokinetic parameters of amikacin were determined in 12 healthy volunteers after a 1-hr continuous intravenous infusion of 7.5 mg of the drug/kg. The serum concentration rose rapidly to a peak of 37.5 +/- 4.9 mug/ml at the termination of the infusion and declined to 1.3 +/- 0.5 mug/ml 8 hr later. The mean half-life was 114 +/- 16.7 min, and the apparent volume of distribution was 18.1% +/- 1.8% of body weight. During a 4-hr constant intravenous infusion in three subjects, amikacin was cleared from the kid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
13
0

Year Published

1978
1978
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 14 publications
6
13
0
Order By: Relevance
“…In the current study, concurrent administration of cefepime and amikacin did not alter the pharmacokinetics of either antibiotic. The pharmacokinetic properties of cefepime before, during, and after amikacin coadministration and those of amikacin before, during, and after cefepime coadministration were in excellent agreement with the previously reported pharmacokinetic properties of these drugs (4,5,9,17,21).…”
Section: Resultssupporting
confidence: 89%
“…In the current study, concurrent administration of cefepime and amikacin did not alter the pharmacokinetics of either antibiotic. The pharmacokinetic properties of cefepime before, during, and after amikacin coadministration and those of amikacin before, during, and after cefepime coadministration were in excellent agreement with the previously reported pharmacokinetic properties of these drugs (4,5,9,17,21).…”
Section: Resultssupporting
confidence: 89%
“…Studies of pharmacokinetic properties of amikacin in adults have shown the volume of distribution to be 0.25 liter/kg, which is similar to the Vd we found (3,4,6,11,16,18). A previous study of amikacin in pediatric patients revealed a Vd of 0.32 liter/kg, but this higher value probably was due to the inclusion of a large number of patients with cystic fibrosis, who have abnormal weight-to-surface area ratios (25).…”
supporting
confidence: 83%
“…A previous study of amikacin in pediatric patients revealed a Vd of 0.32 liter/kg, but this higher value probably was due to the inclusion of a large number of patients with cystic fibrosis, who have abnormal weight-to-surface area ratios (25). The differences in the clinical pharmacology between our pediatric patients and adults can be accounted for by the significantly greater total body clearance of amikacin (131 versus 100 ml/min per 1.73 m2) and shorter half-life (1.24 h in children versus 2.2 h in adults) (3,4,6,11,16,18).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Amikacin, another recently developed semisynthetic aminoglycoside, has proven effective in treatment of various infections, and its toxicity seems to be similar to that of gentamicin (3,6,10 12 h for 7 to 10 days. All patients had complicated urinary tract infections, mainly due to obstruction of the lower urinary tract from benign hyperplasia, prostate or bladder carcinoma, or urethral stricture.…”
mentioning
confidence: 99%